2018
DOI: 10.3390/nano8010028
|View full text |Cite
|
Sign up to set email alerts
|

UV-Vis-Induced Degradation of Phenol over Magnetic Photocatalysts Modified with Pt, Pd, Cu and Au Nanoparticles

Abstract: The combination of TiO2 photocatalyst and magnetic oxide nanoparticles enhances the separation and recoverable properties of nanosized TiO2 photocatalyst. Metal-modified (Me = Pd, Au, Pt, Cu) TiO2/SiO2@Fe3O4 nanocomposites were prepared by an ultrasonic-assisted sol-gel method. All prepared samples were characterized by X-ray powder diffraction (XRD) analysis, Brunauer-Emmett-Teller (BET) method, X-ray photoelectron spectroscopy (XPS), scanning transmission electron microscopy (STEM), Mott-Schottky analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 67 publications
6
32
1
Order By: Relevance
“…), as has been observed for these microspheres [106,108]. Therefore, a mechanically stable core has been proposed, such as magnetic Fe 3 O 4 , which additionally allows the fast and easy separation of photocatalysts after reactions in the magnetic field [109][110][111]. However, the photoreaction between a core and a shell might result in the instability of the photocatalyst (e.g., dissolution of iron), and thus an insulator interlayer has been applied by Zielinska-Jurek et al between a magnetic core and titania shell, as shown in Figure 6 [110].…”
Section: Core-shell Titania Compositesmentioning
confidence: 81%
“…), as has been observed for these microspheres [106,108]. Therefore, a mechanically stable core has been proposed, such as magnetic Fe 3 O 4 , which additionally allows the fast and easy separation of photocatalysts after reactions in the magnetic field [109][110][111]. However, the photoreaction between a core and a shell might result in the instability of the photocatalyst (e.g., dissolution of iron), and thus an insulator interlayer has been applied by Zielinska-Jurek et al between a magnetic core and titania shell, as shown in Figure 6 [110].…”
Section: Core-shell Titania Compositesmentioning
confidence: 81%
“…[13][14][15] Moreover, silver, copper, and zinc nanoparticles revealed biocidal properties 16,17 and metal nanoparticles such as platinum or palladium decrease charge carriers recombination rate on the surface of titanium(IV) oxide. Among commonly used semiconductors, titanium(IV) oxide is one of the most efficient photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…An activation of titanium(IV) oxide under visible light irradiation is possible through surface modification with noble metal nanoparticles such as silver, gold, platinum, and palladium. [13][14][15] Moreover, silver, copper, and zinc nanoparticles revealed biocidal properties 16,17 and metal nanoparticles such as platinum or palladium decrease charge carriers recombination rate on the surface of titanium(IV) oxide. 18 Commercial application of photocatalysis is associated with the costs of photocatalytic process, thus it is essential to look for new environmentally friendly light sources.…”
mentioning
confidence: 99%
“…However, in the presence of AO, the reaction rate even increased to 0.54 ± 0.03• µmol•h −1 , respectively. Previously, for TiO 2 -based magnetic photocatalysts, the rate-enhancing effect of silver ions used as an electron scavenger was reported [56]. The photogenerated electrons can be trapped by Ag + ions inhibiting the rate of the charge carriers recombination.…”
Section: Photocatalytic Activitymentioning
confidence: 99%